New Product Development: The Perspective of SMES in Malaysia - Omar, Siti Sarah; Bujang, Nazarudin; Al-Shameri, Ahmed saleh Ahmed Saif; Khairul, Mohamad (Journal of Techno-Social, 2021)
Small Medium Enterprise (SMEs) are growing rapidly in Malaysia and are the backbone of economic growth. Until today, there are more than 1 million SMEs company registered. The purpose of this research is to determine the best competitive forces and the best practices of New Product Development (NPD). The Porter’s Five Forces Theories or dimensions have been used to determine the competitive forces which is effective for new product development. The targeted population was the top level SME companies in the Southern Region of Malaysia and they are the producer of food and beverages. Data have been collected from 40 top level managers of the selected SME companies using quantitative method. The findings revealed that the best NPD practice is the commercialization, while the best sales competitive forces is threat of substitutes. The owners of the SMEs are recommended to transform their marketing strategies and product innovation to achieve their target and success in the future.